Criminal Law Regulations on Health in Indonesia and Thailand: A Review of the Protection of the Rights of Patients and Medical Personnel - Rubianti, Ni Kadek Sri Novi Wirani; Gorda, A. A. A. Ngurah Tini Rusmini; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The regulation of criminal health law in Indonesia and Thailand differs in legal systems and approaches, where Indonesia follows a civil law system, while Thailand adopts a mixed legal system, impacting legal protection for patients and medical personnel as well as the effectiveness of law enforcement in healthcare services. This study aims to analyze the regulation of criminal health law and the dispute resolution mechanisms in Indonesia and Thailand in ensuring legal protection for patients and medical personnel while balancing the interests of both parties. This research employs a normative legal method with a statutory, comparative, and conceptual approach to analyze criminal health law regulations in Indonesia and Thailand, utilizing literature studies and qualitative analysis to assess the effectiveness of legal protection for patients and medical personnel in both countries. The findings reveal that the regulation of criminal health law in Indonesia and Thailand aims to protect patients and medical personnel but differs in legal systems and medical dispute resolution mechanisms. Indonesia, which adheres to the civil law system, regulates the criminal liability of medical personnel through the Criminal Code (KUHP), the Health Law, and the Medical Practice Law, yet still faces challenges in distinguishing professional negligence from criminal offenses, often leading to the criminalization of medical personnel.. Thailand's more flexible approach reduces the risk of criminalizing medical personnel while ensuring patients receive their rights, whereas Indonesia still needs to develop a more effective compensation system to balance the interests of patients and medical personnel